Decoupled aqueous batteries using pH-decoupling electrolytes - Zhu, Yun-hai; Cui, Yang-feng; Xie, Zi-long; Zhuang, Zhen-bang; Huang, Gang; Zhang, Xin-bo (Nature reviews. Chemistry, 2022)
Aqueous batteries have been considered as the most promising alternatives to the dominant lithium-based battery technologies because of their low cost, abundant resources and high safety. The output voltage of aqueous batteries is limited by the narrow stable voltage window of 1.23 V for water, which theoretically impedes further improvement of their energy density. However, the pH-decoupling electrolyte with an acidic catholyte and an alkaline anolyte has been verified to broaden the operating voltage window of the aqueous electrolyte to over 3 V, which goes beyond the voltage limitations of the aqueous batteries, making high-energy aqueous batteries possible. In this Review, we summarize the latest decoupled aqueous batteries based on pH-decoupling electrolytes from the perspective of ion-selective membranes, competitive redox couples and potential battery prototypes. The inherent defects and problems of these decoupled aqueous batteries are systematically analysed, and the critical scientific issues of this battery technology for future applications are discussed. Developing aqueous batteries with high voltages is possible with the use of pH-decoupling electrolytes with an acidic catholyte and an alkaline anolyte.